Insights into remediation effects and bacterial diversity of different remediation measures in rare earth mine soil with SO42− and heavy metals - Yan, Xiao; Gao, Bowen; Wang, Jianlei; Zhu, Xuezhe; Zhang, Mingjiang (Frontiers in Microbiology, 2023)
A rise demand for rare earth resources has led to an increase in the development of rare earth mines ( REM). However, high concentration leaching agent (SO42- ) and heavy metals result from the process of rare earth mining has increased creating a pressing need for removal of contaminants. Here, a series of experiment with different remediation measures, including control (CK), sulfate-reducing bacteria (SRB) alone (M), chemicals (Ca(OH)2, 1.5 g/kg) plus SRB (CM-L), chemicals (Ca(OH)2, 3.0 g/kg) plus SRB (CM-M), and chemicals (Ca(OH)2, 4.5 g/kg) plus SRB (CM-H), were conducted to investigate removal effect of SO42-, Pb, Zn and Mn from the REM soil. And then, a high-throughput sequencing technology was applied to explore the response of bacterial community diversity and functions with different remediation measures. The results indicated that CM-M treatment had more efficient removal effect for SO42-, Pb, Zn and Mn than the others, up to 94.6%, 88.3%, 98.7% and 91%, respectively. Soil bacterial abundance and diversity were significantly affected by treatments with inoculation of SRB in comparison with CK. The relatively abundance of Desulfobacterota with the ability of transforming SO42- into S2- increased significantly in all treatments except for CK. There was a strong correlation between environmental factors (pH, Eh, SO42-, Pb and Zn) and bacterial community structure. Furthermore, functional prediction analysis revealed that the inoculation SRB treatments increased the abundance of sulfate_respiration, sulfite_respiration and nitrogen_fixation significant increased, while the manganese_oxidation, dark_hydrogen_oxidation and denitrification decreased. This provides good evidence for us to understand the difference of removal efficiency, bacterial community structure and function by different remediation measures that help to select more efficient and sustainable method to remediate contaminants in the REM soil.